Rural income inequality in China since 1978. - Bramall, Chris; Jones, Marion E. (1993)
Official data suggest only a modest increase in rural income inequality in China since 1978. However, these figures significantly understate the true extent of inequality. Using more reliable data, this article shows that an inexorable increase in inequality has been taking place in China over the last decade, a trend apparent both within and between villages. The final two sections of this article outline the underlying causal processes at work in the rural economy
Keywords: Rural poor - China; Income distribution - China